Poverty hits children first? - Fegert, J. M.; Harsch, D.; Kölch, M. (Die Psychiatrie, 2017)
Poverty is a risk factor for mental health problems during childhood and adolescence in general. The economic crisis (2007–2013) seemed to have intensified poverty in families within the most affected countries, esp. in the southern countries of Europe. Within a selective literature review, existing data on the risk of poverty, mental disorders in parents and further risk factors on mental health of children are analyzed. Direct effects like limited access to mental health care system may exist, but are not proved in general. From a developmental perspective, effects of the crisis seem more indirectly mediated by well-known risk factors for psychiatric disorders of children and adolescents: substance abuse in families, mental disorders of parents and loss of perspectives within families are risk factors both on mental health of a child but also for a low educational level which would be a resilience factor. There is evidence that an increase of child abuse and neglect (adverse childhood experiences, ACE) was linked to the economic crisis. Long-term effects e.g. due to ACE may be observed in later times, when children are grown-up.
Keywords: Economic crisis; mental health of children and adolescents; development; risk-factors